Applied clinical pharmacokinetics / Larry A. Bauer - Bauer, Larry A.
Clinical pharmacokinetic and pharmacodynamic concepts -- Clinical pharmacokinetic calculations and equations -- Drug dosing in special populations : renal and hepatic disease, dialysis, heart failure, obesity, and drug interactions -- Aminoglycoside antibiotics -- Vancomycin -- Digoxin -- Lidocaine -- Procainamide/N-acetyl procainamide (NAPA) -- Quinidine -- Phenytoin/fosphenytoin -- Carbamazepine -- Valproic acid -- Phenobarbital/primidone -- Ethosuximide -- Lamotrigine -- Levetiracetam -- Oxcarbazepine/eslicarbazepine -- Cyclosporine -- Tacrolimus -- Sirolimus -- Lithium -- Theophylline